Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1526924816633943
|View full text |Cite
|
Sign up to set email alerts
|

Living Kidney Donors’ Information Needs and Preferences

Abstract: This study revealed limited usefulness of certain CMS-mandated topics and a desire for additional information about donation. Efforts to standardize the informed consent process should incorporate donors' perspectives as to the specific topics, quantity of information, and the mode of communication found most useful when considering living donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…9 Com base nesta teoria, as pessoas formam crenças pessoais sobre sua doença e tratamento, que podem ser agrupadas em várias dimensões: sociodemográfica, doenças relacionadas, consequências do processo de adoecimento, duração, cura, controle e estado emocional. Os conhecimentos sobre a doença e tratamento são passíveis de influenciar e ser influenciados por estas crenças comprometendo igualmente a adaptação à doença.…”
Section: Métodounclassified
See 1 more Smart Citation
“…9 Com base nesta teoria, as pessoas formam crenças pessoais sobre sua doença e tratamento, que podem ser agrupadas em várias dimensões: sociodemográfica, doenças relacionadas, consequências do processo de adoecimento, duração, cura, controle e estado emocional. Os conhecimentos sobre a doença e tratamento são passíveis de influenciar e ser influenciados por estas crenças comprometendo igualmente a adaptação à doença.…”
Section: Métodounclassified
“…Os conhecimentos sobre a doença e tratamento são passíveis de influenciar e ser influenciados por estas crenças comprometendo igualmente a adaptação à doença. [9][10] Os dados foram armazenados em planilha eletrônica para análise estatística no software Statistical Package for the Social Sciences (SPSS ® ). Os dados foram apresentados de forma descritiva; as variáveis categóricas foram expressas em frequências absolutas e relativas e as variáveis numéricas, medidas-resumo (média, quartis, mínimo, máximo e desvio padrão).…”
Section: Métodounclassified
“…Potential recipients may turn down living donor kidney offers to protect the potential donor from incurring risks, or avoid asking people to donate because it is too challenging and/or may make others feel obligated to donate [8]. For living donors, financial barriers may affect LDKT [13, 15, 23]. A prospective study from seven Canadian transplant centers [15] stated 47% of living donors reported a loss of income with the average total out-of-pocket expenses and lost wages of $3,268.…”
Section: Introductionmentioning
confidence: 99%
“…Living donors desire additional information on LDKT beyond the CMS mandated specific information [58]. In addition to information on health risks, financial concerns such as out-of-pocket expenses, lost wages, and insurance obtainment after donation are important for potential recipients and potential donors [13, 15, 23]. Decision aids that address the benefits of transplant, the transplantation process, targeted questions to assist patients make decisions, and financial materials for potential recipients and potential living donors are helpful to understand the breadth of commitment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation